DEVELOPMENT OF SMALL BUSINESS AND ENTREPRENEURSHIP IN EMPLOYMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the cases and problems of organizing small business and family entrepreneurship in the employment of the population.